Pemberdayaan Ekonomi Masyarakat Pesisir Melalui Produksi Kerupuk Atom Ikan: Studi Kasus Di Kabupaten Kepulauan Anambas - Hafifa, Nur; Umaira, Putri Nabilah; Yanti, Dewi; Siahaan, Sonia Trifosa; Firman, Firman (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This study analyzes the potential and challenges of fish cracker (kerupuk atom ikan) production as an economic empowerment strategy for coastal communities in Anambas Islands Regency. Employing a qualitative descriptive approach, the study reveals that fish cracker production has emerged as a form of local resource-based economic adaptation, primarily utilizing skipjack tuna. generates informal employment, and strengthens women's roles in the local economy. Women are the primary actors throughout the production and marketing process, fostering gender-based social transformation in coastal areas. Digital marketing strategies via social media have expanded market access, although challenges remain in licensing, product legality, and production capacity. SWOT analysis indicates strengths in readily available raw materials and unique flavor, but also threats from fluctuating supply and competition from outside the region. Therefore, synergy between the government, entrepreneurs, and supporting institutions is crucial to strengthen institutional capacity, access to capital, and product and marketing innovation. Fish cracker production demonstrates potential as a sustainable economic empowerment model for coastal communities and can be replicated in similar regions.